Intervensi Kompres Hangat Jahe Merah dalam Menurunkan Skala Nyeri Sendi Pada Lansia di BPSTW Budi Luhur DIY - Sofia Ad-Dini; Riyadi, Sujono; Prayitno, Sidik (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
Background: Joint pain is a major problem that is increasingly experienced by the elderly. Pain is felt in the knees, wrists, fingers such as being stabbed, cramped and stiff. Acute pain is the most common symptom that occurs in the elderly with joint disorders. Warm red ginger compresses are one therapy that can be used to reduce acute joint pain. Objective: Intervention of non-pharmacological therapy application of warm red ginger compresses in reducing the scale of joint pain in the elderly at the Budi Luhur BPSTW, DIY Social Service. Method: The study used case reports, namely case study reports containing a description of a problem by exploring nursing care with acute joint pain problems in the elderly at the Budi Luhur BPSTW, DIY Social Service with the implementation of red ginger warm compress intervention. The subject used was one client with joint pain problems who was willing to be an intervention respondent and cooperative. Results: The intervention was conducted for 3 days with acute pain problems related to physiological injury agents. The results of the red ginger warm compress therapy intervention on the first day of acute pain scale 5 and a decrease in the pain scale to 3 on the last day. Conclusion: There was a decrease in the scale of joint pain after non-pharmacological nursing actions of warm red ginger compresses for 3 days were carried out on Mrs. SS.